Pengaruh Social Media Marketing, Review Vlogger Kecantikan Dan Brand Image Terhadap Keputusan Pembelian Lipstick Hanasui (Studi Kasus Produk Lipstick Hanasui di Kota Malang) - Karima, Isnaini; Arifin, Rois; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The purpose of this study is to analyze and determine the influence of social media marketing, beauty vlogger reviews and brand image on the decision to purchase Hanasui lipstick on Instagram. This research uses a positivist philosophy with a quantitative approach. Sampling was carried out at Cosmetic Shops in Malang City using the Sugiyono formula so that the sample in this study was 75 respondents. This research method uses multiple linear regression analysis with SPSS analysis. Hypothesis testing uses the t test and F test. The results of the research show that brand image has a partially significant effect on the decision to purchase Hanasui lipstick on Instagram. Keywords: Social Media Marketing, Vlogger Reviews, Brand Image, And Purchasing Decisions